COVID-19 Pandemic and the Operation of a Tertiary Hospital in Tianjin—The Impact of Internet Healthcare on Hospital Business Indicators - Chen, Jia; Jie, Liu; Su, Xiao; Zhang, Xin; Guo, Dandan; Wang, Jiajing; Deng, Meili; Cui, Mingrui; Gao, Meijian; Zhang, Hong; Song, Yijun (Frontiers in Public Health, 2022)
Objective: To explore the impact of the COVID-19 pandemic on hospital business and the contribution of Internet healthcare to hospital operations during the epidemic by analyzing the degree of impact on major business indicators. Methods: The three-year period from 2019 to 2021 was compared and analyzed, and the main medical business indicators such as outpatient and emergency visits, inpatients, operations, patient improvement rate, cure rate and fatality rate in tertiary hospitals were compared and analyzed, and the impact of the epidemic on medical services and hospital operation was analyzed. degree and the impact of Internet medical development on medical service capacity. Results: During the outbreak of COVID-19, the number of hospital outpatient and emergency visits, inpatients, and operations decreased significantly; after the normalization of the epidemic, the main medical business indicators such as outpatient and emergency visits, inpatients, and operations gradually returned to pre-epidemic levels; patient improvement rate , the cure rate and mortality rate and other indicators did not change significantly. During the epidemic period, the number of visits to the Internet outpatient clinic has increased significantly, which has significantly improved the hospital's medical service capacity. Conclusion: With the normalization of epidemic prevention and control, the main business indicators of Tianjin tertiary hospitals have gradually recovered. The operation of Internet medical care during the epidemic has changed the management and operation mode of the hospital to a certain extent, improved the main business indicators of the hospital, and eased the pressure on the hospital's economic operation.